Between State Law and Islamic Law: The Practice of Divorce Outside the Situbondo Religious Courts, Indonesia - Karim Faiz, Abd.; AR, Zulfahmi; Izzuddin, Ahmad (Journal of Islamic Law, 2022)
The relationship between state law and religion (Islamic law) is still problematic in its implementation. This problem occurs in practising divorce outside the court in Situbondo, Indonesia. Its case is interesting because it is still considered legal by the community and religious leaders according to religious law even though the divorce decision has not been received from the court. This legal phenomenon is contrary to positive law in Indonesia. This article aims to explain the practice of divorce outside the court in Situbondo and the authority problem between state law and Islamic law. After conducting intensive field research for three months with perpetrators of out-of-court divorce, religious leaders, and the Head of the Office of Religious Affairs, the authors found that the widespread practice of divorce outside the court was caused by the influence of religious leaders’ understanding and public understanding. This understanding becomes the doctrine that divorce in Islamic law is legal without having to await a divorce decision from the religious court. The authors stated that the dominance of the authority of Islamic law over state law in the practice of divorce in Muslim societies has negative implications for the rights of children and ex-wives.